Two if by sea [large type] - Mitchard, Jacquelyn (Center Point Large Print, 2016)
"After losing his family in a tsunami in Brisbane, Australia, former police officer Frank Mercy rescues Ian from a submerged car and takes him home to his Midwestern farm. As the boy exhibits a telepathic gift, Frank and new love Claudia will travel to England to keep him safe from a sinister group who want him back"--